Edgar Dale's Pyramid of Learning in medical education: A literature review. (November 2013) - Masters, Ken
<x xml:space="preserve">Abstract</x> Background: Edgar Dale's Pyramid of Learning and percentages of retained learning are cited in educational literature in a range of disciplines. The sources of the Pyramid, however, are misleading. Aims: To examine the evidence supporting the Pyramid and the extent to which it is cited in medical education literature. Methods: A review of literature (1946–2012) based on a search utilising Academic Search Complete, CINAHL, Medline and Google Scholar conducted from September to November 2012. Results: A total of 43 peer-reviewed medical education journal articles and conference papers were found. While some researchers had been misled by their sources, other authors' interpretations of the citations did not align with the content of those citations, had no such citations, had circular references, or consulted questionable sources. There was no agreement on the percentages of learning retention, in spite of many researchers' citing primary texts. Discussion and conclusion: The inappropriate citing of the Pyramid and its associated percentages in medical education literature is widespread and continuous. This citing undermines much of the published work, and impacts on research-based medical education literature. While the area of learning/teaching strategies and amount of retention from each is an area for future research, any reference to the Pyramid should be avoided.